Comparison of specimen adequacy in fine-needle aspiration biopsies performed by surgeons and pathologists - Al-Marzooq, Yusef M. (Ann Saudi Med, 2004)
BACKGROUND: Fine-needle aspiration biopsy (FNAB) may yield different results depending on its operator. We compared the proportions of unsatisfactory aspirates obtained by pathologists vs. surgeons. METHODS: In a retrospective review, all FNAB reports and slides performed between March 2002 and February 2003 were grouped by organ/site and according to whether they were done by a pathologist or a surgeon. The proportions of unsatisfactory aspirates for pathologists and surgeons were compared. RESULTS: Of 692 FNABs, 390 were performed by pathologists at the FNAC clinic and the remainder by surgeons. Overall, 15.5% of aspirates obtained were unsatisfactory (n=107). Of aspirates obtained by surgeons, 29.5% were unsatisfactory, compared to 4.6 % of those obtained by pathologists (P<0.001). Pathologists had significantly lower proportions of unsatisfactory aspirates in all sites. A 33% reduction in the number of lymph node excisional biopsies has been reported subsequent to establishment of the FNAC clinic. CONCLUSIONS: The advantages of a pathologist performing FNAB are that a rapid evaluation can be rendered regarding specimen adequacy and the need for repeating the procedure. In addition, pathologists can direct the distribution of aspirated material for other tests such as culture study, flow cytometry and electron microscopy, as indicated by preliminary evaluation of the smears. These factors significantly lower the proportions of unsatisfactory specimens and improve the diagnostic accuracy of FNAB technique.